Concentrations of para-Fluorofuranylfentanyl in Paired Central and Peripheral Blood Collected during Postmortem Death Investigations. Issue 4 (10th March 2021) - Rodriguez Salas, Judith; Krotulski, Alex J; Newman, Reta; Thogmartin, Jon R; Mohr, Amanda L A; Logan, Barry K
Abstract: The opioid epidemic in the USA has been associated with an increasing mortality rate in large part due to the emergence and proliferation of synthetic opioids over the last 15 years. Fentanyl and its analogs have played a large part in these statistics due to their potency and toxicity. Fluorofuranylfentanyl (FFF) is a fentanyl analog that emerged in the USA in 2018 and was associated with numerous adverse events and deaths. During this study, a liquid chromatography tandem mass spectrometry workflow was developed to accurately identify the isomer of FFF present ( ortho- vs. meta- vs. para- ) in medicolegal death investigation cases from Pinellas County, Florida. FFF was quantified in central and peripheral blood samples collected at autopsy. In addition, the metabolism of FFF was studied using liquid chromatography quadrupole time-of-flight mass spectrometry. para- FFF was quantitatively confirmed in 29 postmortem cases; no other isomer of FFF was detected. Central blood concentrations ranged between 0.66 and 73 ng/mL (mean = 11 ± 14 ng/mL, median = 10 ng/mL) and peripheral blood concentrations ranged between 0.53 and 23 ng/mL (mean = 5.7 ± 6.4 ng/mL, median = 2.7 ng/mL). A comparison of central to peripheral blood concentrations was evaluated to determine the possibility of postmortem redistribution. The metabolism of ortho- FFF was studied and found to undergo metabolic processes similar to fentanyl, producing ortho- fluorofuranyl-norfentanyl, fluoro-4-anilino- N -phenethylpiperidine, and hydroxylated species. The results of this study demonstrate the toxicity of FFF and its implication in medicolegal death investigations. Laboratories must remain aware of new or re-emerging fentanyl analogs, as they pose significant risks to public health and public safety.